CEFD: Centro de Educação Física e Desportos - Pires Andrade, Livia; Rodrigues de Carvalho, Hevilyn; de Oliveira Paradela, Thálisson; Mesquita Silva, Richard Bruno; Azevedo Feltmann Silva, Suzana; Rosa Carvalho, Ingrid; Chicon, José Francisco; Silva Santana, Ana Paula; da Silva, Erineusa Maria; Souza Chagas, Stephane; Ribeiro Silva Gomes, Lígia; Castardeli, Edson; et al. (Revista Guará, 2023)
Resumos dos projetos do Centro de Educação Física e Desportos